Rural local authorities and investment attraction: the case of Umzingwane Rural District Council - Dube, Khulani (Midlands State University, 2014)
The research topic came after realisation that UMzingwane Rural District Council was failing to attract investment despite having vast natural resources, a tarred main road and a railway line. In order to carry out the intended purpose the research objectives and research questions were out lined to guide the research on the topic: Rural Local Authorities and investment attraction. The case of UMzingwane Rural District Council. Relevant Literature was used to explore the viewsofother scholars pertaining to rural investmentattraction.The definition of investment and the types of investment were discussed in the literature review. This section also evaluates the factors influencing investment, the types of industries that can invest in rural local authorities. Lastly strategies that can be used to attract rural investment were discussed. The researcher used an exploratory research design. The research study was mostly qualitative in nature with some quantitative elements. The case study technique was adopted. The case study technique was adopted to avoid generalising the findings of the research. Convenience sampling was used to sample the population for this research.Those respondents who were accessible were questionnaired and interviewed. Questionnaires, interviews and observations were used to solicit data. The major findings of this research are that UMzingwane Rural District Council has not created enough policies to attract investment; the council has vast resources that include gold, fish, water and tourist attracting sites.